Absorption and scattering of massless scalar waves by black holes in quasi-topological gravity - Sihao Fan; Chen Wu; Wenjun Guo (European Physical Journal C: Particles and Fields)
Abstract We consider massless scalar field perturbations of regular black holes in quasi-topological gravity. After reviewing various regular black hole solutions, we compute the total absorption cross-section and the partial absorption cross-section for different choices of the parameters using the partial wave method. The results show that the larger the parameter $$α $$ α , introduced in the context of quasi-topological gravity, the smaller the total absorption cross-section. In addition, we find that the influence of the space-time dimension D on the absorption and scattering of massless scalar waves in this set of regular black holes differs from earlier computations.